Tourism, Economic growth, Environment, Human Capital and Political Instability: Heterogeneous linkages - Shahzad, Muhammad; Azam, Ali (iRASD Journal of Economics, 2023)
This study aims to estimate heterogeneous causal linkages among tourism, economic growth, environment, human capital and political instability for all economies in the world. In this study, we used the global panel data, which consists of the world. The study employs the fixed effects model (FEM) to estimate the panel regression model. Results indicate that in all models, economic growth attracts tourism, and tourism increases economic growth. Tourism and CO2 are negatively related. Tourism and human capital are positively related, and political instability and tourism are also positively related. The study concluded that environmental emissions and economic growth are negatively related. Our research shows a positive connection between economic growth and human capital. Economic growth and political instability are negatively related. Environment emission and human capital are negatively related. Our results have shown that political instability and CO2 are positively related to each other. Political instability and human capital are negatively related. Results have shown that human capital hurts political insatiability. Findings suggest that host countries should not only promote tourism but also ensure that the environment is not degraded, so green tourism needs to be promoted in order to ensure that the development process will remain smooth and sustainable. To promote sustainable tourism development and economic growth, governments should concentrate on economic policies and allocate more resources to human capital management. Tourism policymakers need to be aware of the dimensions of political instability and its likely impact on their industry.